Antioxidant and Physicochemical Properties of Hydrogen Peroxide‐Treated Sugar Beet Dietary Fibre. (1st March 2016) - Mišan, Aleksandra; Sakač, Marijana; Medić, Đorđe; Tadić, Vanja; Marković, Goran; Gyura, Julliana; Pagano, Ester; Izzo, Angelo A.; Borrelli, Francesca; Šarić, Bojana; Milovanović, Ivan; Milić, Nataša
Abstract : The aim of the present work was to examine if hydrogen peroxide treatment of sugar beet fibre that aimed at improving its physicochemical properties would impair its antioxidant potential. Three different sugar beet fibres were obtained from sugar beet – non‐treated fibre (NTF) from sugar beet cossettes extracted with sulphurous acid, treated fibre (TF) from NTF treated with hydrogen peroxide in alkaline solution and commercially available Fibrex ® . The antioxidant activity of extractable and non‐extractable fibre fractions in ethanol/water mixture (80:20, v/v) of three fibre samples was estimated. Non‐extractable fractions obtained after alkaline treatment of investigated fibres were much higher in phenolic compounds and possessed higher antioxidant potential than extractable fractions. Ferulic acid was proven to be the dominant phenolic acid. Regarding both extractable and non‐extractable fractions, Fibrex ® had the highest antioxidant activity in chemical tests, while NTF was superior in comparison with TF. Based on the results of Caco‐2 cells‐based test, all non‐extractable fractions possessed potential for reactive oxygen species inhibition. Regarding the extractable fractions, only the TF manifested this effect.Copyright © 2016 John Wiley & Sons, Ltd.